Immediate Postpartum Intrauterine Contraceptive Device Insertions in Caesarean and Vaginal Deliveries: A Comparative Study of Follow-Up Outcomes. (17th August 2016) - Hooda, Reetu; Mann, Sonika; Nanda, Smiti; Gupta, Anjali; More, Hemant; Bhutani, Jaikrit
Abstract : Background . Immediate postpartum intrauterine contraceptive device (IPPIUCD) is a lucrative postpartum family planning method which provides effective reversible contraception to women in the delivery setting. Our aim was to study the clinical outcomes of IPPIUCD insertions and compare them as a factor of route of insertion (vaginal versus caesarean). Methods . This is a retrospective analytical study done in a tertiary care teaching institute. A Cohort of 593 vaginal and caesarean deliveries with IPPIUCD insertions, over a two-year period, was studied and compared for follow-up results. Outcome measures were safety (perforation, irregular bleeding, unusual vaginal discharge, and infection), efficacy (pregnancy, expulsions, and discontinuations), and incidence of undescended IUCD strings. Descriptives were calculated for various outcomes and chi square tests were used for comparison in between categorical variables. Results . Overall complication rates were low. No case of perforation or pregnancy was reported. Spontaneous expulsions were present in 5.3% cases and were significantly higher in vaginal insertions (p = 0.042 ). The incidence of undescended strings was high (38%), with highly significant difference between both groups (p = 0.000 ). Conclusion . IPPIUCD is a strong weapon in the family planning armoury and should be encouraged in both vaginal and caesarean deliveries. Early follow-up should be encouraged to detect expulsions and tackle common problems.